Assessment of port-related air quality impacts: geographic analysis of population. (2015) - Arunachalam, Saravanan; Brantley, Halley; Barzyk, Timothy M.; Hagler, Gayle; Isakov, Vlad; Kimbrough, Evelyn S.; Naess, Brian; Rice, Nathan; Snyder, Michelle G.; Talgo, Kevin; Venkatram, Akula
Increased global trade has led to greater transportation by rail, road and ships to move cargo. Based upon multiple near-road and near-source monitoring studies, the busy roadways and large emission sources at ports may impact local air quality within several hundred metres of the ports. Health effects have been associated with near-road exposures and proximity to large emission sources, so characterising emission sources is important for understanding potential health effects. To address this need, we have developed a new community-scale tool called C-PORT to model emissions related to all port-area activities and predict concentrations of multiple criteria and hazardous air pollutants at fine spatial scales in the near-source environment. We present a geographical information system analysis of areas surrounding five US ports (Ports of New York and New Jersey, Virginia, Savannah, Miami, and Houston) to determine potential sources of concern related to freight transport and demographics of the near-source population that could be affected.